Optimizing the Potential of Domestic Small Firm: The Case of ICT in Indonesia with a Focus on Management and Skills, and Collaboration in Entrepreneurial Ecosystems - Mahavianti Syamsuri, Liza (International Journal of Social Science, Education, Communication and Economics, 2024)
The rapid growth of the ICT market in Indonesia is driven by a young and prosperous population. However, domestic SMEs are struggling to meet the increasing demand. This paper analyzes the internal and external factors affecting innovation in ICT firms. The findings suggest that ICT skills, market-related skills, management experience, and cognitive capability are positively related to innovation. Additionally, improving ICT education and emphasizing modern management is identified as a key challenge. The paper also recommends enhancing value co-creation in local communities, particularly between small firms and local customers, and between foreign firms and local small firms.